2017
DOI: 10.1088/1361-6528/aa9f07
|View full text |Cite
|
Sign up to set email alerts
|

Thermal conductivity anisotropy in holey silicon nanostructures and its impact on thermoelectric cooling

Abstract: Artificial nanostructures have improved prospects of thermoelectric systems by enabling selective scattering of phonons and demonstrating significant thermal conductivity reductions. While the low thermal conductivity provides necessary temperature gradients for thermoelectric conversion, the heat generation is detrimental to electronic systems where high thermal conductivity are preferred. The contrasting needs of thermal conductivity are evident in thermoelectric cooling systems, which call for a fundamental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 45 publications
1
25
0
Order By: Relevance
“…In crystalline structures, Umklapp scattering dominates the phonon transport at the temperature range of interest, which shortens the phonon mean free path and leads to a reduction in the thermal conductivity with the temperature. The thermal conductivity of crystalline samples κ C is computed using the Callaway model 44 , which is expressed aswhere the average phonon relaxation time τ is computed combining phonon-grain boundary , film boundaries , phonon-impurity , Umklapp , phonon-carrier , and, in the case of Ag 3.9 Sb 33.6 Te 62.5 films, nanoprecipitate scattering mechanisms as 4547 , where D is the average grain size , P is the phonon transmission across the grain boundary, t is the thickness of the film, n NP is the nanoprecipitate number density, and Θ is the average nanoprecipitate scattering cross-section, which is estimated using the average nanoinclusion size, and the mass and tensor strength difference with the matrix 17,48 . As detailed at the beginning of this section, the thickness of the film is measured using cross-sectional SEM imaging and the grain size is derived from the XRD spectra.…”
Section: Resultsmentioning
confidence: 99%
“…In crystalline structures, Umklapp scattering dominates the phonon transport at the temperature range of interest, which shortens the phonon mean free path and leads to a reduction in the thermal conductivity with the temperature. The thermal conductivity of crystalline samples κ C is computed using the Callaway model 44 , which is expressed aswhere the average phonon relaxation time τ is computed combining phonon-grain boundary , film boundaries , phonon-impurity , Umklapp , phonon-carrier , and, in the case of Ag 3.9 Sb 33.6 Te 62.5 films, nanoprecipitate scattering mechanisms as 4547 , where D is the average grain size , P is the phonon transmission across the grain boundary, t is the thickness of the film, n NP is the nanoprecipitate number density, and Θ is the average nanoprecipitate scattering cross-section, which is estimated using the average nanoinclusion size, and the mass and tensor strength difference with the matrix 17,48 . As detailed at the beginning of this section, the thickness of the film is measured using cross-sectional SEM imaging and the grain size is derived from the XRD spectra.…”
Section: Resultsmentioning
confidence: 99%
“…In recent studies, silicon nanostructures with vertically etched holes, or holey silicon, had demonstrated significant thermalconductivity reductions and anisotropic thermal conductivity in the in-plane and cross-plane directions [56][57][58]. Ren and Lee had shown that the unique thermal-conductivity anisotropy in holey silicon is ideal for thermoelectric cooling (TEC) to address onchip hot spots [59,60]. In the in-plane direction, the neck size dominated phonon boundary scattering reduces the thermal conductivity (k x and k y ), which sustains a large temperature gradient for enhanced thermoelectric effects.…”
Section: Recent Progress In Thermal Metamaterialsmentioning
confidence: 99%
“…For 3D packages, thermal metamaterials based on bending or shifting designs could be used to guide the heat efficiently toward heat sinks and facilitate heat dissipation through HBM stacks. Thermal management of 3D stacks could be further addressed by optimal arrangements of TSVs and potential use of silicon-based thermoelectric cooling elements [34,36,37,39,59,61,132,136]. Several studies discussed the potential use of thermal metamaterials for circuit designs [15,19,20,152].…”
Section: Cooling Capacities Of One Package To System Levelmentioning
confidence: 99%
“…Unlike isotropic materials, the thermal conductivity of anisotropic materials is different in different directions, enabling preferential heat transfer in one direction compared to another. Thermal anisotropy allows heat to dissipate in a preferential direction, and has been investigated for improved heat dissipation and hot spot remediation in electronics [10][11][12][13]. Suszko and El-Genk [11] numerically investigated thermally anisotropic composite heat spreaders comprised of two 0.5 mm thick copper (Cu) laments separated by a thin (0.25-1.0 mm) layer of graphite to achieve in-plane thermal conductivities of 200-325 W/(mK) and cross-plane conductivities of 5-20 W/(mK).…”
Section: Introductionmentioning
confidence: 99%
“…The composite spreaders were predicted to remove up to 429% higher heat than an all-Cu spreader [11]. Conversely, Ren and Lee [13] utilized the high cross-plane conductivity and low in-plane conductivity of holey silicon nanostructures to achieve improved thermoelectric cooling effectiveness compared to high-thermal conductivity bulk silicon.…”
Section: Introductionmentioning
confidence: 99%